Development, Validation and Standardization of Instrument to Measure Statistical Literacy among Universities Undergraduates in Cross River State - Usani Joseph Ofem; Isaac Ubi Ofem; Samuel Akpan; Sylvia Victor Ovat; C. E. Nworgwugwu; Bernard Otu; Cletus Akpo Atah (Richtmann Publishing, 2022)
The study developed, validated, and standardised a statistical literacy test for university undergraduates in Cross River State, Nigeria. Five research questions were raised to guide this study. The study adopted an instrumentation design. A stratified sampling technique was used to select a total of 753 respondents from a population of 4705 students. Three instruments were used to collect data: the Statistical Literacy Test (SLT), the Statistical Reasoning Test (SRT), and the Statistical Anxiety Test (SAT). Descriptive statistics (means and simple percentages), correlational analysis, and the factor analytical technique were used to analyse the data collected. The result showed that only 25 items survived the last item assessment. The instrument was found to have strong construct validity as the items in the correlation matrix were all positively correlated. The statistical literacy scale showed convergence with statistical reasoning but diverged with statistical anxiety. The reliability of the instrument was found to be high as the coefficients of the scale were 0.81, 0.77, and 0.78 respectively, and it was adjudged reliable. Based on the findings of the study, it was concluded that the instrument was valid and reliable. Thus, it was recommended that students' skills in statistics should not just be on the computational aspect but on the utilisation of statistical knowledge. Statistics lecturers should emphasise statistical literacy to help students reason and think statistically, and the instrument should be widely distributed for use by researchers and psychometricians. Received: 16 August 2022 / Accepted: 28 October 2022 / Published: 5 November 2022